Solid-state oxygen separation from air using imidazolium-functionalized anion exchange membranes - Zhang, Manman; Suslonova, Anna; Zhong, Jinliu; He, Xuezhong; Dekel, Dario R. (Frontiers in Membrane Science and Technology, 2025)
The energy-efficient extraction of oxygen directly from air remains a significant technological challenge. Anion-exchange membranes (AEMs) play a critical role in electrochemical systems due to their ability to provide high ionic conductivity and chemical stability, achieved through rational design of polymer backbones combined with functional cationic groups. In this study, we combine fuel cell and water electrolyzer electrodes to allow a unique electrochemical device to selectively extract oxygen from air. Specifically, we present a hydrophilic imidazolium group that was introduced as a “performance-assisting moiety” onto a poly (2,6-dimethyl-1,4-phenylene oxide) (PPO) backbone to fabricate novel AEMs. The resulting membranes exhibited controlled water uptake of 21.2%–53.7%, moderate swelling ratios of 3.5%–18.3% below 70 °C, and satisfactory thermal and mechanical stability. Selected AEMs that demonstrated moderate ionic conductivity and ion exchange capacity (IEC) were incorporated into an electrochemical anion exchange membrane oxygen separator (AEMOS). The resultant device can achieve a high current density of 109 mA cm-2, reflecting its strong potential for efficient oxygen separation. This work presents a promising solid‐state and electrolyte‐free strategy for oxygen extraction, which is expected to contribute to the development of sustainable oxygen generation technologies.